The blockchain technologies: Do we really know what we are talking about? - (:unkn) unknown (My University, 2022)
The purpose of this study is to give insights into individuals’ perceptions of blockchain technologies (BCT). A model is constructed to explore drivers of BCT use and tested empirically using structural equation modeling (SEM) to survey data. Data is collected from a sample of 300 working individuals with engineering and business backgrounds and a multi-item questionnaire is used. Results indicated that reputation affects attitude towards BCT through perceived usefulness and perceived risk and intention to do transactions via BCT can be explained by attitude towards BCT. Intention to use BCT was quite high among the respondents and interestingly their educational backgrounds did not have any effect.

Bu çalışmanın amacı, bireylerin blok zincir teknolojilerine (BZT) ilişkin algılarını incelemektir. BZT kullanımını etkileyen unsurları keşfetmek için oluşturulan teorik model yapısal eşitlik modellemesi (YEM) kullanılarak ampirik olarak test edilmiştir. Araştırmada veriler, mühendislik ve işletme eğitimi geçmişine sahip 300 çalışandan oluşan bir örneklemden toplanmış ve çok maddeli bir anket kullanılmıştır. Sonuçlar, itibarın algılanan fayda ve algılanan risk üzerinden BZT’ye karşı tutumu etkilediğini ve BZT’ye karşı tutumun BZT aracılığıyla işlem yapma niyeti ile açıkladığını göstermekledir. Katılımcılar arasında BZT’yi kullanma niyeti oldukça yüksek bulunmuştur ve ilginç bir şekilde sonuçlar eğitim geçmişlerinin istatistiksel olarak anlamlı bir etkisi olmadığını ortaya koymaktadır.
Keywords: Blockchain technologies (BCT); Perceived usefulness; Perceived risk; Reputation; Attitude towards BCT; Blokzincir teknolojileri (BZT); Algılanan fayda; Algılanan risk; İtibar; BZT’ye karşı tutum